ChemInform Abstract: Divergent Synthesis of 2, 6‐Diaryl‐Substituted 5, 7, 8‐Trimethyl‐1, 4‐benzoxazines via Microwave‐Promoted Palladium‐Catalyzed Suzuki—Miyaura Cross Coupling and Biological Evaluation. Issue 19 (18th April 2013) - Koini, Eftychia N.; Avlonitis, Nicolaos; Martins‐Duarte, Erica S.; de Souza, Wanderley; Vommaro, Rossiane C.; Calogeropoulou, Theodora
Abstract Compounds (III) inhibit Toxoplasma gondii tachyzoite proliferation, exhibiting inhibition concentration values in the low micromolar range.